2013
DOI: 10.4049/jimmunol.1202386
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors GATA-3 and RORγt Are Important for Determining the Phenotype of Allergic Airway Inflammation in a Murine Model of Asthma

Abstract: In refractory asthma, neutrophils, rather than eosinophils, often predominate in the airways. Neutrophilic airway inflammation appears to be resistant to steroids and may be related to the Th17, rather than the Th2, cytokine milieu. However, the role of GATA-3 and RORγt, transcription factors for Th2 and Th17 cell differentiation, respectively, in the pathogenesis of steroid-insensitive asthma remains unclear. To examine the effect of GATA-3– and RORγt-overexpression backgrounds on airway inflammation and ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 42 publications
3
78
1
Order By: Relevance
“…It has been reported that this chemokine is upregulated in lung epithelial and endothelial cells during inflammation (49), suggesting that epithelial and endothelial cells might contribute to the production of CXCL5 enhanced by the cooperative action of IL-33 and IL-17A. It has been reported that Ag-induced AHR, neutrophilic inflammation, and ELR + CXC chemokine production, such as CXCL1 and CXCL2 in experimental asthmatic models associated with IL-17A using Th17 cell-reconstituted SCID and RORgt-tg mice, were steroid resistant (50,51). Consistent with these data, we found that dexamethasone failed to inhibit coadministration of IL-33-and IL-17A-induced AHR, neutrophilic inflammation, and ELR + CXC chemokine production, indicating that AHR and neutrophilic inflammation exacerbated by IL-33 and IL-17A were also steroid resistant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this chemokine is upregulated in lung epithelial and endothelial cells during inflammation (49), suggesting that epithelial and endothelial cells might contribute to the production of CXCL5 enhanced by the cooperative action of IL-33 and IL-17A. It has been reported that Ag-induced AHR, neutrophilic inflammation, and ELR + CXC chemokine production, such as CXCL1 and CXCL2 in experimental asthmatic models associated with IL-17A using Th17 cell-reconstituted SCID and RORgt-tg mice, were steroid resistant (50,51). Consistent with these data, we found that dexamethasone failed to inhibit coadministration of IL-33-and IL-17A-induced AHR, neutrophilic inflammation, and ELR + CXC chemokine production, indicating that AHR and neutrophilic inflammation exacerbated by IL-33 and IL-17A were also steroid resistant.…”
Section: Discussionmentioning
confidence: 99%
“…7A). The expression of MIP-2 is significantly elevated in ovalbumin-dependent mouse model of asthma (30). In allergic airway inflammation, the expression of MIP-2 is increased (31).…”
Section: Mip-2 Is Regulated By Mir-26a/-26b and Cox-2-cytokinementioning
confidence: 94%
“…Several other groups have generated Tg mice with overexpression of Gata3 and have consistently reported enhanced eosinophilic airway inflammation (33)(34)(35)(36). In chronic models that involve repeated allergen exposure, enforced Gata3 expression was associated with increased subepithelial fibrosis and airway smooth muscle hyperplasia (35).…”
Section: Discussionmentioning
confidence: 99%
“…These CD2-Gata3 Tg mice lacked Th1-mediated hypersensitivity responses and showed reduced differentiation or activity of the Th17 cell subset, and protection from autoimmune encephalomyelitis and rheumatoid arthritis (29,31,32). Overexpression of Gata3 in T cells has been associated with enhanced Th2 responses and eosinophilic airway inflammation in vivo (33)(34)(35)(36). However, effects of Gata3 overexpression on the ILC2 population in AAI remain unknown.…”
mentioning
confidence: 99%